The Neuroimaging Contribution to the Schizophrenia Diagnosis and Monitoring: A Brief Systematic Review [Contribución de la Neuroimagen Al Diagnóstico y Seguimiento de la Esquizofrenia: Una Breve Revisión Sistemática] - Labbe-Atenas, T (Sociedad de Neurologia Psiquiatria y Neurocirugia, 2022)
Introduction: Structural and functional neuroimaging in schizophrenia has gained strength in recent years, so this review aims to describe neuroimaging findings that contribute to the physiopathological understanding, monitoring, and diagnosis of this pathology. Methods: A PubMed/Medline search was conducted for clinical studies addressing neuroimaging in schizophrenia. Results: The search yielded 2200 results, from which 13 studies were included, which provided findings, such as functional and structural alterations of the amygdala, which have shown to be associated with negative symptoms; morphometric reduction of the frontal region, alterations in the perfusion of the anterior cingulate gyrus and the lower-left parietal cortex, deregulation of the histone deacetylase enzyme, among others which translate clinically in neurocognitive deficits. Conclusions: This review provides an updated view on the findings of neuroimaging that can contribute to the understanding of the pathological mechanisms behind this psychotic disorder, its diagnostic usefulness, and its potential contribution to the prognosis and follow-up of this disease. © 2022 Sociedad de Neurologia Psiquiatria y Neurocirugia. All rights reserved.